Development of competencies of pediatric residents and teachers in screening and surveillance of preschool children - Caguioa, Maria Cristina R.
A gap is seen in the implementation of screening and surveillance of children in the out-patient setting and in the community. Pediatric residents and teachers should undergo a training workshop to transfer appropriate knowledge and skills to strengthen screening and surveillance in their workplace. The objectives of the study are to (1) determine the effect of training on the competencies of residents and teachers in screening and surveillance of preschool children and (2) determine the acceptability and usefulness of doing screening and surveillance using the Filipino-translated 60-month ages and stages questionnaire (ASQ).